The Role of Digitalization of Learning Media in Shaping the Learning Discipline of Muhammadiyah Bogor High School Students - Al-Khatib, Ibadurrahman (Journal of Education Technology and Inovation, 2025)
The goal of education nationally is to improve the quality of the Indonesian population, namely people who believe and devour God Almighty, have noble character, are disciplined, work hard, are tough, responsible, independent, intelligent, capable, physically and spiritually healthy. In the last two decades, the learning process has undergone significant transformation through the Digitalization of learning media. This study analyzes the role of digitalization of learning media in shaping the learning discipline of Muhammadiyah High School students in Bogor city. The research methodology used is a descriptive qualitative approach. The research subjects include religious teachers, students of classes X and XI of SMA Muhammadiyah in Bogor. The results of the study show that the Digitalization of learning media has a positive role in the formation of student learning discipline at SMA Muhammadiyah Bogor. This learning Digitalization process is effective with the synergy between school policies, the role of teachers, and the implementation of innovative digital media, so that the strengthening of learning discipline aspects in Muhammadiyah High School students in Bogor city is formed.